Needs and Targeting - Michael Michael Keen (Queen's University, Department of Economics, 1991)
This paper shows that when - in the manner of the recent targeting literature - the resources available for poverty relief are allocated across heterogeneous groups so as to minimize a 'well-behaved' index of aggregate poverty, the optimal response to an increase in the needs of some group may be to reduce the resources allocated to it. Necessary and sufficient conditions for optimally-targeted benefits to be inversely related to needs are established under two polar forms of poverty alleviation strategy (pure contingency and strict means-testing) and the wider methodological implications of this possibility discussed.
Keywords: O243; 915; 330; poverty; social security; needs